IMPROVING THE SUPERVISION PROCESS: TRUST, PRESENCE, EMPOWERMENT AND RECOGNITION - Benigno, Stephen D (Advances in Social Sciences Research Journal, 2017)
Trust, presence, empowerment and the recognition of success are four administrative strategies that can facilitate a successful implementation of the new instructional supervision models. The recent initiatives involving the effective and formative supervision of instruction in the public school systems essentially require more than just an effective model of supervision. The relationship between the administration and the instructional staff that has traditionally involved simply an observation, a walk-through, check sheet and has resulted in a summative and terminal evaluation of instruction, will definitely require a paradigm shift. The new models emphasize a collaborative and communicative relationship between the teachers and the school administration. The utilization of the four administrative strategies may facilitate the collaboration and communication necessary to achieve the successful Implementation and delivery of the new models of instructional supervision. The development and improvement of instruction and student learning outcomes in our schools will be dependent on that collaborative and communicative relationship.